2004
DOI: 10.1117/12.537195
|View full text |Cite
|
Sign up to set email alerts
|

Design and fabrication of advanced EUV diffractive elements

Abstract: As extreme ultraviolet (EUV) lithography approaches commercial reality, the development of EUV-compatible diffractive structures becomes increasingly important. Such devices are relevant to many aspects of EUV technology including interferometry, illumination, and spectral filtering. Moreover, the current scarcity of high power EUV sources makes the optical efficiency of these diffractive structures a paramount concern. This fact has led to a strong interest in phase-enhanced diffractive structures. Here we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The multilayer grating refers to etching/depositing multilayers in the shape of gratings on the substrate of the collector [ 48 , 49 ] . Spiller [ 50 , 51 ] first suggested using reflective multilayers to improve the EUV reflectivity of the grating [ 52 ] . Figure 11 depicts the schematic of the rectangular multilayer grating.…”
Section: Integrated Spectral Purity Filters On the Collectormentioning
confidence: 99%
See 1 more Smart Citation
“…The multilayer grating refers to etching/depositing multilayers in the shape of gratings on the substrate of the collector [ 48 , 49 ] . Spiller [ 50 , 51 ] first suggested using reflective multilayers to improve the EUV reflectivity of the grating [ 52 ] . Figure 11 depicts the schematic of the rectangular multilayer grating.…”
Section: Integrated Spectral Purity Filters On the Collectormentioning
confidence: 99%
“…Generally, the DE of the multilayer blazed grating is affected by the quality of the saw-tooth facets, smoothness of the substrate and groove density, and the former two are the main challenges. Naulleau et al [ 52 , 55 , 56 ] proposed a method of fabricating the blazed grating and decreased the roughness caused by the substrate by smoothing the optimized multilayers, which presented an evident smoothing effect, while it was at the cost of the profile fidelity. Naulleau et al [ 55 ] and Liddle et al [ 57 ] identified the conditions for topography control while fabricating the blazed grating with hydrogen silsesquioxane (HSQ), and achieved a relative EUV efficiency of 63%.…”
Section: Integrated Spectral Purity Filters On the Collectormentioning
confidence: 99%
“…Even amplitude structures with the lowest possible efficiency, such as diffractive elements are commonly used in UV to focus the radiation [ 22 ]. For this frequency range there is the lack of materials introducing phase shifts that are transparent [ 23 , 24 ]. Thus, there is a need to optimize the thickness of diffractive elements (illustrated in Figure 1 , the exact explanation of all mechanisms is given in the following sections of this review).…”
Section: Characteristic Features Concerning Manufacturingmentioning
confidence: 99%
“…For a π phase shift thickness of 86 nm at 13.5-nm wavelength, Mo still transmits 60% of the power supporting surprisingly efficient phase devices. 9 Figure 3 (a) and (b) provide some tolerance requirements for grating fabrication.…”
Section: Theoretical Efficiency and Design Requirementsmentioning
confidence: 99%
“…In addition to binary gratings, gray-scale e-beam exposure methods capable of high resolution three-dimensional pattering have been used in fabricating both blazed gratings 3 and EUV diffusers. 4,5 Similarly, these methods also suffer from the response of the multilayer coating to the underlying resist topography. To address this issue we consider patterning phase-modulating structures on top of or directly into the multilayer.…”
Section: Introductionmentioning
confidence: 99%